Underlying Reasons for Marked and Unmarked Code-Mixed Expressions in Advertisement Jingles - Oso, Mary Temiloluwa; Babalola, Emmanuel Taiwo; Uwalaka, Edith Nkechinyere; Irabor, Yemisi Folasade (Journal of Natural Language and Linguistics, 2025)
The linguistic practice of code-mixing in advertisements can be unmarked or expected to occur, or sometimes marked or unanticipated by the listeners, which has some underlying reasons for its occurrence. The objective of this study is to examine the marked and unmarked code-mixed expressions used by the advertisers in the selected Southwestern Nigerian Radio and online advertisement jingles and the underlying reasons why the advertisers make these language choices. The primary source of data was drawn from 60 code-switched advertisement jingles collected from 30 radio commercials and 30 online advertisements on YouTube through purposive random sampling technique. The 30 radio jingles were collected from 12 radio stations in the Southwestern states in Nigeria which are Osun, Oyo, Ondo, Ogun, Ekiti and Lagos. In each of the states, a private radio station and a public radio station were selected. The result showed that the advertisers made use of both marked and unmarked code-mixing which have some underlying reasons why the advertisers made use of these language choices. All these marked and unmarked choices ultimately contribute to the successful dissemination of the proposed messages regarding the advertised products and services to people in the multilingual Nigerian society. It is therefore recommended that rather than viewing code-mixing as an indication of linguistic incompetence, the advertisers should harness it as a viable communicative instrument to ensure the listeners are able to grasp important information about the marketed goods and services in a multilingual society.